A Review of Geometric Reconstruction Algorithm and Repairing Methodologies for Gas Turbine Components - Haidong Wu; Jian Gao; Si Li; Yaohui Zhang; Detao Zheng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Repairing of the used gas turbine components is becoming a challenge due to continual increase in manufacturing costs and the complex geometry. This paper discusses research on the repairing solutions for the damaged ones. The various kinds of geometric reconstruction algorithm for those are introduced selectively from the cross-section of the blade because of its vital roles. However, owing to the limitation of the algorithm, it has been lack of an efficient approach for reconstructing the geometry of a blade. As a result of this study, future research directions are highlighted. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2311